1997
DOI: 10.1074/jbc.272.34.21075
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Amiloride Binding Domain within the α-Subunit of the Epithelial Na+ Channel

Abstract: Limited information is available regarding domains within the epithelial Na؉ channel (ENaC) which participate in amiloride binding. We previously utilized the anti-amiloride antibody (BA7.1) as a surrogate amiloride receptor to delineate amino acid residues that contact amiloride, and identified a putative amiloride binding domain WYRFHY (residues 278 -283) within the extracellular domain of ␣rENaC. Mutations were generated to examine the role of this sequence in amiloride binding. Functional analyses of wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
54
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 40 publications
2
54
1
Order By: Relevance
“…5C). However, it has been reported that mutation of residues at a site in the extracellular domain also disrupted block by amiloride, raising the possibility that amiloride might block the channel indirectly through an allosteric mechanism (35). If this is the case, then the site between Gly 533 and Gly 536 might not be a binding site for amiloride, but rather the site of a conformational change that occludes the pore in response to the binding of amiloride to a distant site.…”
Section: Discussionmentioning
confidence: 92%
“…5C). However, it has been reported that mutation of residues at a site in the extracellular domain also disrupted block by amiloride, raising the possibility that amiloride might block the channel indirectly through an allosteric mechanism (35). If this is the case, then the site between Gly 533 and Gly 536 might not be a binding site for amiloride, but rather the site of a conformational change that occludes the pore in response to the binding of amiloride to a distant site.…”
Section: Discussionmentioning
confidence: 92%
“…However, previous studies have identified a region in the extracellular loop of rat ␣-ENaC between amino acids 278 and 283, with the sequence WYRFHY, that interacts with amiloride (12). When this stretch of amino acids, located just COOH terminal to the first transmembrane-spanning domain within a cysteinerich domain, is deleted or mutated, amiloride binding of these channels expressed in a bilayer system is dramatically reduced.…”
mentioning
confidence: 99%
“…open probability; extracellular loop; channel pore; sodium channel; single-channel recording EPITHELIAL SODIUM CHANNELS (ENaC) play a critical role in the control of blood pressure and regulation of total body sodium balance. Although the original work in which the channel components were cloned suggested that functional channels consist of three subunits, ␣, ␤, and ␥ (5), under appropriate circumstances, ␣-subunits alone can form sodium-permeable channels (12,13,17). It has been proposed that some of the diversity in conductance, gating, and selectivity of functional ENaC may be due to different subunit combinations.…”
mentioning
confidence: 99%
“…Recent work examining the properties of channels composed solely of ␣-subunits identified a domain within the extracellular loop of ␣-rENaC (residues 278 -283) where mutations or deletions affect amiloride block as well as the open probability of the channels (14,17). Furthermore, selected mutations within this region of ␣-ENaC or within the corresponding region of ␥-ENaC altered the channel's response to external Ni 2ϩ (27) and to changes in extracellular Na ϩ (26).…”
Section: Discussionmentioning
confidence: 99%
“…In channels composed solely of ␣-subunits, mutations in this domain affect both channel gating and channel block by amiloride (14,17). This region within the ␣-subunit includes residues 278 -283 (WYRFHY).…”
mentioning
confidence: 99%